2021
DOI: 10.3892/etm.2021.10864
|View full text |Cite
|
Sign up to set email alerts
|

Management of psoriasis in children (Review)

Abstract: Psoriasis is a common long-lasting, inflammatory disease that mainly affects the skin. The incidence of this condition has increased significantly over time and at this point, it affects approximately 1% of children. Psoriasis can appear at any age, including childhood and adolescence, with a higher frequency in girls, an earlier onset being associated with severe psoriasis. The pathology is the result of the interaction between genetics and trigger factors such as infections, stress, diet, obesity, and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…7 Immunological factors include interactions between various kinds of immune cells, such as T-helper cell 1 (Th1), Th17, Th22, mast cells, and neutrophils, and abnormal expression of cytokines. 6 One review reported that the onset of psoriasis primarily involves the cytokines such as interferon (IFN)-γ, tumor necrosis factor (TNF)-α, and interleukin (IL)-17, IL-22, and IL-23 and that an imbalance between effector T cells, such as Th-17, and regulatory T cells plays a role in the etiology of psoriasis. 7,18 Moreover, the onset of psoriasis may involve LL-37, an antimicrobial peptide that activates plasmacytoid dendritic cells and keratinocytes, leading to the production of various inflammatory cytokines.…”
Section: E Tiology and Clinic Al Symp Toms Of Ped Iatri C Psoria S Ismentioning
confidence: 99%
See 2 more Smart Citations
“…7 Immunological factors include interactions between various kinds of immune cells, such as T-helper cell 1 (Th1), Th17, Th22, mast cells, and neutrophils, and abnormal expression of cytokines. 6 One review reported that the onset of psoriasis primarily involves the cytokines such as interferon (IFN)-γ, tumor necrosis factor (TNF)-α, and interleukin (IL)-17, IL-22, and IL-23 and that an imbalance between effector T cells, such as Th-17, and regulatory T cells plays a role in the etiology of psoriasis. 7,18 Moreover, the onset of psoriasis may involve LL-37, an antimicrobial peptide that activates plasmacytoid dendritic cells and keratinocytes, leading to the production of various inflammatory cytokines.…”
Section: E Tiology and Clinic Al Symp Toms Of Ped Iatri C Psoria S Ismentioning
confidence: 99%
“…The onset of pediatric psoriasis involves various factors, including the stress associated with starting school, separation from parents, mechanical trauma, and infection 7 . Immunological factors include interactions between various kinds of immune cells, such as T‐helper cell 1 (Th1), Th17, Th22, mast cells, and neutrophils, and abnormal expression of cytokines 6 . One review reported that the onset of psoriasis primarily involves the cytokines such as interferon (IFN)‐γ, tumor necrosis factor (TNF)‐α, and interleukin (IL)‐17, IL‐22, and IL‐23 and that an imbalance between effector T cells, such as Th‐17, and regulatory T cells plays a role in the etiology of psoriasis 7,18 .…”
Section: Etiology and Clinical Symptoms Of Pediatric Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Распространенность псориаза в детской популяции составляет 0,7% и линейно увеличивается с возрастомот 0,2% в возрасте до 1 года и до 2,5% в возрасте 18 лет [7,8]. За последние 50 лет показатель заболеваемости псориазом детей увеличился более чем вдвое [9,10]. Вместе с этим установлено, что ранняя манифестация псориаза связана с более тяжелым течением болезни, высоким риском развития коморбидных патологий (инсулинорезистентность, сахарный диабет 2-го типа, эндотелиальная дисфункция, артрит), в том числе сердечно-сосудистых заболеваний, особенно при наличии отягощенного семейного анамнеза [2,10].…”
Section: Clinical Observationunclassified
“…Psoriasis is a chronic, papulosquamous, inflammatory skin disease that presents with abnormal hyperproliferation of the epidermis, morphologically resulting in well‐demarcated, scaly pink‐colored plaques in white skin and hyperpigmented, brownish‐gray plaques in the skin of color 1,2 . Though any skin surface may be involved, psoriatic plaques most often occur on the scalp and extensor aspects of knees and elbows with characteristic bilateral symmetry 1 .…”
Section: Introductionmentioning
confidence: 99%